Analisis Gaya Bahasa Satire Dan Pesan Pada Rubrik Lincak Surat Kabar Harian Solopos - Keumala Nurhidayat, Koko; , Prof. Dr. Markhamah, M.Hum (2016)
This research is aim to know (1) how to describe the use of language style "Satire" on rubrics lincak Solopos' daily newspaper (2) how to identify the meaning which consist on on rubrics lincak Solopos' daily newspaper. This data sources used in this research was daily newspapers Solopos. The method of collecting data which used in this research is a method that take the paragraph show the language style of satire. The analysis method which used by padan method, a method which used referential of pilah referents as a benchmark.The result showed that (1) there is language style of satire, like as language criticsm and language of mockery, (2) there is moral value. That moral values are respectful, manners behave, and confident. The social value is coordination and cooperation. (3) demand improvements were found, among others: (a) government to have to set the rules on sending workers, (b) Using kewengangan already given, (c) subsidies as a form of public services, (d) subsidies as a form of public services , (e) Improve the legal system in Indonesia, (f) Concern between people (mutual cooperation), (g) Maintain Indonesian from the entry of foreign languages, (h) Confident and sticking to its founding. (I) Loyalty in every organization and is responsible, (j) Maintaining the integrity of the nation, (k) Politics intelligently and aspirations of the people, (l) Prove yourself to artists who are members of the board, (m) Consistent and well-behaved, ( n) Ready to K-13 curriculum, (o) Right, and conscientious in reporting (News).